The Impact of Artificial Intelligence AI in Team-Based Project TBPj on Undergraduate Students' Meta-skills - Astriawati, Fitri; Mardiyanti, Lely (FKIP Universitas Lampung, 2023)
Abstract: The rapid transformation of the world due to advances in science and technology encourages universities to develop students' meta-skill competencies to adapt to various changes in world work. This research aims to investigate the impact of artificial intelligence (AI) integrated team-based project (TBPj) on the development of undergraduate students’ meta-skills. This study employed a quasi-experimental design using one group pre-test and post-test design with 30 research subjects. Data were collected using a meta-skills instrument in the form of a questionnaire and analyzed using a paired sample t-test. The results revealed a significant difference between the mean meta-skill scores of the students before (M = 37.50, SD = 13.31) and after (M = 86.57, SD = 4.30) the treatment [t(36) = 13.884, p < 0.001; d = 4.20]. Based on the results, it can be concluded that the use of AI integrated with the TBPj model has a high impact on improving undergraduate students' meta-skills. Keywords: artificial intelligence AI, team-based project TBPJ, meta-skills Abstrak: Cepatnya transformasi dunia akibat kemajuan ilmu pengetahuan dan teknologi mendorong perguruan tinggi untuk mengembangkan kompetensi meta-skills mahasiswa agar lebih adaptif terhadap berbagai perubahan dunia kerja. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan artificial intelligence (AI) terintegrasi team-based project (TBPj) terhadap pengembangan meta-skills mahasiswa. Studi ini adalah quasi eksperimen menggunakan rancangan one group pre-test and post-test design dengan subjek penelitian sebanyak 30 orang. Data dikumpulkan dengan menggunakan instrument meta-skills berbentuk kuisioner dan dianalisis menggunakan uji statistic paired sample t-test. Hasil penelitian menunjukkan perbedaan signifikan antara rata-rata skor meta-skills mahasiswa sebelum (M = 37.50, SD = 13.31) dan setelah (M = 86.57, SD = 4.30) perlakuan [t(36) = 13.884, p <0.001; d = 4,20]. Berdasarkan hasil tersebut dapat disimpulkan bahwa penggunaan AI terintegrasi model TBPj berdampak tinggi terhadap perbaikan meta-skills mahasiswa Kata kunci: artificial intelligence AI, team-based project TBPJ, meta-skills DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp825-836